PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA DAN KNOWLEDGE SHARING TERHADAP KEPUASAN KERJA PADA KARYAWAN CV. SARANA INTI PERTAMA - Andar Saulu; Dyah Ayu Puri Palupi (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
This study examines how knowledge sharing, work environment, and work motivation affect workers' job satisfaction at CV. Sarana Inti Pertama. The following theories are put forth in this study: H1: Employee job satisfaction is suspected to be influenced by work motivation; H2: Employee job satisfaction is suspected to be influenced by work environment; H3: Employee job satisfaction is suspected to be influenced by knowledge sharing; and H4: Employee job satisfaction is simultaneously influenced by work motivation, work environment, and knowledge sharing.In order to get insight, a quantitative research approach including surveys and interviews is employed. Research that use questionnaires as the main means of gathering data from samples of a population is known as survey research. Purposive sampling, which is predicated on particular factors or standards, is the sampling technique employed. 38 workers participated in this investigation as responders. A multiple linear regression model was used to analyze the data using SPSS 31.0.2, 2023.The data analysis revealed that the knowledge sharing variable had a t-value of 28.968, the work environment variable was 28.046, and the work motivation variable was 53.640. In the meanwhile, 2.034 is the t-table value. The study's findings suggest that employee job satisfaction at CV. Sarana Inti Pertama is partially and concurrently influenced by work motivation, work environment, and knowledge sharing.